Interaction of national and international law: constitutional and legal basics - Yerzhanova, F.A.; Abylasimov, M.N. (Bulletin of the Karaganda University “Law Series”, 2021)
In this article, based on the study and analysis of the current constitutional legislation of the Republic of Kazakhstan and foreign countries, scientific literature, topical issues of constitutional and legal regulation of the interaction of national and international law in Kazakhstan and foreign countries are considered. The central place is given to the study of the Constitutions that establish the relationship between domestic and international law, an analysis of various approaches of the Basic Laws to consolidating the interaction of international and domestic law is given. The authors highlight theoretical and practical issues related to the interaction of international and constitutional law. By means of comparative legal analysis the authors reveal the characteristic features and peculiarities of regulation by the Constitutions of the correlation of national and international law. It has been established that in the context of general globalization and internationalization of law the domestic Constitution as a whole corresponds to the world tendencies in the development of constitutionalism. In order to improve the constitutional and legal regulation of the interaction of domestic and international law, further scientific development of theoretical and practical issues related to the definition of the concept and content of generally recognized principles and norms of international law, their role and place in the hierarchy of national legal systems is necessary. The authors propose to include in the constitutional legislation a provision that human and civil rights and freedoms in the Republic of Kazakhstan are recognized and guaranteed in accordance with generally recognized principles and norms of international law and in accordance with the Constitution.